PENERAPAN IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM MENINGKATKAN KUALITAS PELAYANAN ADMINISTRASI PADA DINAS KESEHATAN KABUPATEN DELI SERDANG - Reitandi, Reitandi; Aslami, Nuri; Nurbaiti, Nurbaiti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Total Quality Management (TQM) is a management approach that aims to improve the quality of products and services by involving all elements of the organization and focusing on customer satisfaction. In the context of administrative services at the Deli Serdang District Health Service, the implementation of TQM is expected to increase efficiency, accuracy and customer satisfaction in the health administration process. This research aims to analyze and implement the application of TQM in improving the quality of administrative services at the Deli Serdang District Health Service. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the implementation of TQM has a positive impact on improving the quality of administrative services. The implementation of TQM has helped increase the efficiency of administrative processes, reduce errors in data processing, strengthen communication between units at the Deli Serdang District Health Service. In addition, through the TQM approach, awareness of the importance of service quality and the role of each individual in the organization increases.